Psychoneurologic characteristics of patients with type 2 diabetes mellitus and diabetic polyneuropathy - Natalya Alexandrovna Belyakova; Daria Gennad'evna Mikhaylova; Inna Gennad'evna Tsvetkova; Svetlana Alekseevna Gorbacheva; Alexander L'vovich Startsev; Anna Alexandrovna Larina (Сахарный диабет, 2010)
Aim. To study psychologic and neurologic characteristics and their interrelationship in patients with type 2 diabetes mellitus (DM). Materials and methods. The study included 167 women aged 54.2?0.4 years with DM2 9.9?0.51 years in duration. Severity of DM was estimatedfrom the presence of late complications and labile clinical course of the disease. Diabetic peripheral polyneuropathy was diagnosed basedon clinical symptoms, NSS and NDS scales. The psychological status was studied by the Spielberger-Khanin method with the assessment of reactive(situational (PX-1) and personal (PX-2) anxiety. Results. Most CD2 patients presented with moderate (NDS) and severe (NSS) polyneuropathy. It became aggravated as DM duration increased,with subjective symptomatics prevailing over objective one. The psychologic status of the patients was characterized by moderate depression andfrequent anxiety episodes in which personal anxiety prevailed over situational one. The latter was associated with macroangiopathy and thelatter with severe polyneuropathy. Depression most frequently occurred in patients with CHD, obesity, and decompensated carbohydrate metabolism. Conclusion. The above peculiarities of psychologic and neurologic status of DM2 patients should be taken into account when planning their outandinpatient treatment and education.